Income-Leisure Tradeoffs of Animal Workers - Battalio, Raymond C.; Green, Leonard; Kagel, John H. (American Economic Review, 2016)
Results of recent empirical and theoretical research have shown the applicability of consumer demand theory in describing and predicting choices of nonhuman consumers (see A. Covich, D. Rapport and J. Turner, Battalio et al., Kagel et al., 1975, 1980). Commodities used in these studies have been largely limited to different kinds of edibles: food grains, water, and sweet tasting (preferred) fluids. A natural extension of the commodity choice model is to consider leisure as a good. This paper presents results of experiments showing that nonhuman workers (pigeons) are willing to trade off income for leisure if the price is right. More specifically our results show that the Slutsky-substitution effect is positive for (exactly) compensated wage decreases, and that leisure is a normal good at all points in the choice space. In addition to demonstrating the pervasiveness of income-leisure tradeoffs, the experiments show strong regularities in the size of the substitution and income effects at varying wage rates; with increases in real wages both income and substitution effects get smaller, but the substitution term decreases more rapidly than the income term resulting in a backward bending labor supply curve at higher wages. The plan of the paper is as follows. In Section I we characterize the procedures employed in the laboratory for studying labor supply, and summarize well-established characteristics of this behavior as it is relevant to the present experiments. Sections II and III describe the hypotheses tested and the experimental procedures employed in the tests. Results of the experiments are given in Section IV. Some of the implications of these results are discussed in a brief concluding section. Space considerations do not permit a detailed discussion of the reasons why economists should take seriously the investigation of economic theories using nonhuman subjects (see Kagel and Battalio for this argument). For the more skeptical reader we simply note that if one defines economics as .. . .the study of the allocation of scarce resources among unlimited and competing uses (Albert Rees, 1968, p. 472), then animal psychologists, ecologists and biologists have been involved in studying economic behavior for some time now (Rapport and Turner; Jack Hirschleifer; H. Rachlin). It is but a small step to take the technologies of these related disciplines and apply them to behavior of interest to economists, for example labor supply behavior. At a minimum, such studies expand considerably the scope for comparative economic analysis. At a maximum they provide a laboratory for identifying, testing, and better understanding general laws of economic behavior. Use of this laboratory is predicated on the fact that behavior as well as structure vary continuously across species, and that principles of economic behavior would be unique among behavioral principles if they did not apply, with some variation, of course, to the behavior of nonhumans.